KAJIAN BANJIR BANDANG DI DESA SUKOLILO MELALUI TINJAUAN PETA SUNGAI - Prayitno, Hermain Teguh (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2017)
ENGLISHFlash floods often occur in the Sukolilo sub district, Pati Regency Central Java, in particular at Sukolilo village. The high intensity of rainfall in the Sukolilo’s catchment area producing high water volume and flow leads to flash floods in the Sukolilo village one hour after the rainfall. It is an interesting phenomenon because the river located in the Sukolilo village experiences flash flood more frequent compared to other rivers in Sukolilo sub district. This research was conducted by comparing rivers in the Sukolilo sub district through quantitative descriptive method with secondary data. The result of this study showed that the morphology of Sukolilo River has the highest catchment area 300 meter above sea level (ASL) and has narrow downstream 20 ASL. According to the calculation, 3 rivers in the Sukolilo sub district has the potential to experience flash flood that are river located in Sukolilo Village, river located in Wegil Village and river located in the border of of Baleadi Village and Kedung Winong Village, consecutively. INDONESIABanjir bandang di Kecamatan Sukolilo Kabupaten Pati Jawa Tengah sering terjadi terutama di Desa Sukolilo. Debit air yang besar serta kecepatan aliran yang tinggi menyebabkan sungai meluap dan mengkhawatirkan warga yang tinggal di sekitar sungai. Hal tersebut disebabkan intensitas hujan yang sangat tinggi di daerah tangkap sungai Sukolilo yang turun satu jam sebelumnya. Kondisi banjir bandang ini menjadi fenomena tersendiri dikarenakan hanya sungai Sukolilo yang sering terjadi. Maka penelitian ini perlu dilakukan dengan cara membuat studi perbandingan sungai-sungai di wilayah Kecamatan Sukolilo melalui metode deskriptif kuantitatif dengan data sekunder. Hasil penelitian menunjukkan bentuk morfologi sungai Sukolilo memiliki daerah tangkap tertinggi 300 meter di atas permukaan laut (DPL) terluas dari sungai sekitarnya dan mengecil di daerah hilir 20 meter DPL. Urutan tertinggi dari rata-rata skor potensi bandang pertama yaitu Sungai Desa Sukolilo, kedua sungai Desa Wegil, dan ketiga sungai perbatasan antara Desa Baleadi dan Desa KedungWinong.